Selection of Frequency Estimation of 6-10 kV-Overhead Lines’ Technical Condition Based on Reliability Statistical Studies - Basmanov V.G.; Kholmanskikh V.M. (Problems of the Regional Energetics, 2020)
The aim of this work is to justify a criterion selection for the frequency estimation of the 6-10 kV-overhead lines’ technical condition (OL), using the reliability indicators of the overhead lines (failure intensity, mean time between failures, reconditioning intensity and recovery mean time). To achieve the goal a retrospective method was used for obtaining information on reliability and a statistical method for analyzing the reliability of the multiple-action products to justify the frequency criterion. Certain methods of mathematical statistics were applied to process the information obtained. In particular, the Kolmogorov criterion was used to support the hypothesis on the exponential law of distribution of the OL failures and the time of their recovery. Based on the analysis of the 6-year overhead line failures database, the exponential law hypothesis of distribution of the overhead line failures and the time of their recovery was accepted and confirmed. The most essential result is the experimental and theoretical confirmation that the complex indicator of reliability, i.e., the technical preparedness coefficient with account of self-eliminating failures, can be used as the frequency criterion for verification of the OL technical condition. High precision of the criterion has been proved even at a small number of failures. Significance of the results obtained consists in that, while controlling the dynamics of the coefficient and comparing it with the normative values with respect to the OL reliability category, it is possible in due time to fix a date for the OL technical condition checking.